Heterogeneous catalytic hydrogenation of CO2 by metal oxides: defect engineering – perfecting imperfection. (21st June 2017) - Jia, Jia; Qian, Chenxi; Dong, Yuchan; Li, Young Feng; Wang, Hong; Ghoussoub, Mireille; Butler, Keith T.; Walsh, Aron; Ozin, Geoffrey A.
Abstract : In this review, we discuss how metal oxides with designed defects can be synthesized and engineered, to enable heterogeneous catalytic hydrogenation of gaseous carbon dioxide to chemicals and fuels. Abstract : Metal oxides with their myriad compositions, structures and bonding exhibit an incredibly diverse range of properties. It is however the defects in metal oxides that endow them with a variety of functions and it is the ability to chemically tailor the type, population and distribution of defects on the surface and in the bulk of metal oxides that delivers utility in different applications. In this Tutorial Review, we discuss how metal oxides with designed defects can be synthesized and engineered, to enable heterogeneous catalytic hydrogenation of gaseous carbon dioxide to chemicals and fuels. If this approach to utilization and valorization of carbon dioxide could be developed at industrially significant rates, efficiencies and scales and made economically competitive with fossil-based chemicals and fuels, then carbon dioxide refineries envisioned in the future would be able to contribute to the reduction of greenhouse gas emissions, ameliorate climate changes, provide energy security and enable protection of the environment. This would bring the vision of a sustainable future closer to reality.